2017
DOI: 10.1371/journal.pone.0176972
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of gemcitabine plus docetaxel in Japanese patients with unresectable or recurrent bone and soft tissue sarcoma: Results from a single-institutional analysis

Abstract: BackgroundCombination therapy with gemcitabine and docetaxel has been reported to be a good therapeutic strategy for patients with soft tissue sarcoma. The aim of the present study was to analyze the efficacy and toxicity of gemcitabine with docetaxel in Japanese patients with advanced bone and soft tissue sarcoma.Patients and methodsWe retrospectively analyzed the effect of gemcitabine and docetaxel therapy on overall response, progression-free survival, overall survival, and toxicity in 42 patients with bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 28 publications
(48 reference statements)
0
13
0
Order By: Relevance
“…Doctors have tried to apply the same regimen in this set of patients. Unfortunately, the results of the studies using the same dosage and schedule in OS as that in STS were controversial and the number of patients was relatively small, ranging from 4 to 35 [ 11 18 , 27 , 28 ]. We used the GT in refractory metastatic OS from 2012 to 2017 and used the collected data to investigate the value of GT as salvage therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Doctors have tried to apply the same regimen in this set of patients. Unfortunately, the results of the studies using the same dosage and schedule in OS as that in STS were controversial and the number of patients was relatively small, ranging from 4 to 35 [ 11 18 , 27 , 28 ]. We used the GT in refractory metastatic OS from 2012 to 2017 and used the collected data to investigate the value of GT as salvage therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, GT was used as a second-line chemotherapy and response data was reported in ten of them [ 11 18 , 23 , 24 , 27 , 28 ]. These studies are reviewed in Table 4 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Five single-institution studies including a variety of tumor types have shown a collective objective response rate of 29% in the 16 cumulative patients with Ewing sarcoma. [3][4][5][6][7] However, in prospective multi-institutional trials for relapsed Ewing sarcoma, the response rate for 80 total patients was only 12%. 8,9 In the one study involving newly diagnosed patients with Ewing sarcoma, two cycles of GEM/DOC were used as an upfront window to treat 17 evaluable higher-risk patients.…”
Section: Introductionmentioning
confidence: 99%
“…Docetaxel is a semisynthetic member of the taxoid class of antineoplastic agents. Docetaxel-based chemotherapy targeting sarcomatous components is currently used in several areas, such as bone, soft tissue or gynecological sarcomas, and showed favorable response rates (Hensley et al 2008;Takahashi et al 2017;Choi et al 2018). Thus, DCF that could be effective for both carcinomatous and sarcomatous components may be a rational option of preoperative chemotherapy for patients with esophageal carcinosarcoma.…”
Section: Discussionmentioning
confidence: 99%